Recalcitrant psoriasiform dermatosis of the face: Is it related to pityriasis rubra pilaris?. (23rd April 2018) - Gan, Emily Yiping; Ng, See Ket; Goh, Chee Leok; Lee, Siong See Joyce
Abstract : Background: There are patients with recalcitrant psoriasiform plaques that do not fit into conventional categories of facial dermatoses. Our study aims to describe the clinicopathological characteristics of several patients with a unique presentation of persistent psoriasiform facial rashes. Methods: This retrospective cross‐sectional study analyzed clinical and histological data of known cases of recalcitrant psoriasiform dermatosis of the face diagnosed at National Skin Centre, Singapore, over 10 years. Results: There were 8 Chinese patients with mean age at onset of 29 years. Majority had pink to pink‐orange well‐defined plaques with dry scale ( n  = 6, 75%), distributed mostly on the cheeks (100%) and chin ( n  = 7, 88%). Hyperkeratosis, parakeratosis, preserved granular layer and psoriasiform hyperplasia were showed in all biopsies. Other common findings included subtle subcorneal acantholysis, "checkerboard" alternating ortho‐/parakeratosis, vacuolated keratinocytes and follicular plugging. All patients showed little treatment response. One patient eventually developed features of type II pityriasis rubra pilaris (PRP). Our study was limited by its small sample size and lack of a pre‐existing diagnostic code. Conclusions: This recalcitrant psoriasiform facial dermatosis seems to be a distinct entity, with consistent and reproducible clinical features and a PRP‐like histology, bearing some resemblance to the recently described condition—facial discoid dermatosis.